A randomized controlled study of remimazolam in preschool children undergoing adenotonsillectomy - Wu, Yong; Wang, Fenjun; Zhu, Kai; Ling, Li; Zhang, Wangping (Frontiers in Pharmacology, 2025)
BackgroundAt present, remimazolam is widely used for general anesthesia. However, the literature on the usability of remimazolam is limited in preschool children. This study aimed to explore effects of remimazolam on emergence agitation and adverse events in preschool children undergoing adenotonsillectomy.MethodsA total of 100 children undergoing adenotonsillectomy, randomly divided into the Remimazolam group and the Propofol group, with 50 cases in each group. The Remimazolam group received remimazolam for the induction and maintenance of general anesthesia, and the Propofol group received propofol for the induction and maintenance of general anesthesia. The onset time, extubation time and awakening time were recorded. Systolic blood pressure (SBP), diastolic blood pressure (DBP) and heart rate (HR) were measured before anesthesia (T0), immediately before intubation (T1), 3 min after intubation (T2), 15 min after the start of the surgery (T4) and at the end of the surgery (T5). The drug-related complications including hypotension, bradycardia, injection site pain, respiratory depression, emergence agitation, nausea and vomiting were recorded.ResultsThe onset time was significantly longer in the Remimazolam group (64.3 ± 8.1 vs. 38.3 ± 4.5 s, P < 0.001), while the extubation time and awakening time were shorter in the Remimazolam group than the Propofol group (12.9 ± 2.2 vs. 14.5 ± 3.2 min, P = 0.005; 19.9 ± 4.7 vs. 21.8 ± 4.5 min, P = 0.039, respectively). The incidence of emergence agitation, hypotension and injection site pain was lower in the Remimazolam group than the Propofol group (12% vs. 30%, P = 0.027; 26% vs. 48%, P = 0.023; 4% vs. 48%, P < 0.001, respectively).ConclusionThis study demonstrated that remimazolam not only shortened extubation and awakening times but also reduced the incidence of emergence agitation, hypotension, and injection site pain in preschool children undergoing adenotonsillectomy compared with propofol.Clinical Trial Registrationhttps://www.chitr.org.com, identifier: ChiCTR240085456.